2015
DOI: 10.1177/1559325815583761
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Effect of Achillea millefolium L Against Genotoxicity Induced by Ionizing Radiation in Human Normal Lymphocytes

Abstract: The radioprotective effect of Achillea millefolium L (ACM) extract was investigated against genotoxicity induced by ionizing radiation (IR) in human lymphocytes. Peripheral blood samples were collected from human volunteers and incubated with the methanolic extract of ACM at different concentrations (10, 50, 100, and 200 μg/mL) for 2 hours. At each dose point, the whole blood was exposed in vitro to 2.5 Gy of X-ray and then the lymphocytes were cultured with mitogenic stimulation to determine the micronuclei i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…In order to protect the cells from oxidative damage inflicted by radiation, various chemical based radioprotective drugs, namely, WR2721, AET, 2-MPG, and amifostine, were being used. Major handicap of these drugs is that they have inherent toxicity of their own [ 7 , 8 ]. Chemical radioprotectors were found to interfere with the normal immune-stimulatory and pharmacokinetic mechanism by which cell milieu can self-repair.…”
Section: Introductionmentioning
confidence: 99%
“…In order to protect the cells from oxidative damage inflicted by radiation, various chemical based radioprotective drugs, namely, WR2721, AET, 2-MPG, and amifostine, were being used. Major handicap of these drugs is that they have inherent toxicity of their own [ 7 , 8 ]. Chemical radioprotectors were found to interfere with the normal immune-stimulatory and pharmacokinetic mechanism by which cell milieu can self-repair.…”
Section: Introductionmentioning
confidence: 99%
“…32, No.2 (2019) The study demonstrated that the most effective and safe dose of ACM for radioprotection specially for radiotherapy is 200µg/ml. Shahani et al (2015) stated that ACM at a high concentration (200µg/ml) completely normalized DNA damage induced by ionizing radiation on human lymphocytes. This finding goes hand to hand with the proposed effective dose.…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation (IR) produces reactive oxygen species (ROS) such as OH O , H 2 O 2 , OH O , O 2-. These toxic substances represent highly chemical reactive and can react with cellular biomolecules including proteins, lipids, and DNA, resulting in varieties of oxidative lesions (Shahani et al, 2015). Elevated ROS level has been suggested to be involved in cellular dysfunction and death.…”
Section: Introductionmentioning
confidence: 99%
“…Соответственно, можно утверждать об избирательности проявления экстракта на генотоксические свойства этопозида. Так как экстракты других лекарственных растений использовались как в больших, так и в малых концентрациях для проявления антигенотоксических свойств [25], то предоставляется целесообразным проверить данную гипотезу и в отношении используемого нами экстракта P. grandiflora. SMART.…”
Section: среднее Max Minunclassified